Strategy to improve human resource performance in construction services companies - Rodhi, Nova Nevila (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to identify factors that influence human resource performance, analyze factors that should be considered most in improving human resource performance, and analyze strategies that can be implemented to improve human resource performance in construction service companies. Methodology/approach: This study uses a descriptive approach. In general, the methodology used is to combine qualitative research with quantitative research using a case study and a survey approach. The fixed respondent design chosen in this study was the cluster sampling method. The analysis method used in this study is the Analytical Hierarchy Process (AHP) Results/findings: This study produced three conclusions: 1. The results of the identification process based on the literature review obtained several factors that were grouped into four criteria: competence, motivation, loyalty aspects, and work discipline, 2. The competency factor must be considered most in improving the performance of human resources in the construction project of high-rise buildings in Bojonegoro is the competency factor, 3. Strategies that can be carried out to improve performance based on competency include adding staff/workers, providing compensation, providing facilities, providing training, and carrying out control. Limitations: This research was conducted at a construction services company that handles the construction of high-rise buildings in Bojonegoro District, East Java, Indonesia; therefore, the research results need to be developed for larger projects. Contribution: Academically, the benefit of this research is that it can serve as a reference for managing human resources effectively. Novelty: This research can provide new insights into strategies to improve human resource performance so that activities can run more smoothly and provide maximum results.